2019
DOI: 10.1007/s00784-019-03126-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of temporomandibular joint luxation: a systematic literature review

Abstract: Objectives To evaluate the effectiveness of surgical and nonsurgical treatment of temporomandibular joint (TMJ) luxation. Materials and methods This systematic literature review searched PubMed, the Cochrane Library, and Web of Science databases to identify randomized controlled trials on TMJ luxation treatment published between the inception of each database and 26 March 2018. Results Two authors assessed 113 unique abstracts according to the inclusion criteria and read nine articles in full text. Eight artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 33 publications
0
11
0
5
Order By: Relevance
“…Non-surgical methods should have failed before any minimally invasive or open surgical intervention is considered in acute dislocation [4,10]. Minimally invasive techniques for recurrent dislocation include Botulinum toxin injection [34][35][36][37], sclerotherapy [24,38,39], and autologous blood injection (ABI) [40][41][42][43][44][45][46][47]. The best evidence thus far is for the use of ABI with level of evidence Ib [40].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical methods should have failed before any minimally invasive or open surgical intervention is considered in acute dislocation [4,10]. Minimally invasive techniques for recurrent dislocation include Botulinum toxin injection [34][35][36][37], sclerotherapy [24,38,39], and autologous blood injection (ABI) [40][41][42][43][44][45][46][47]. The best evidence thus far is for the use of ABI with level of evidence Ib [40].…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the joint disc can lead to symptoms such as joint popping and difficulty opening the mouth. Disorders of the joint disc often require surgical treatment, but surgery in the TMJ area is often complex and can result in complications [ 281 ]. It has been shown that fibrochondrocytes can be used as seed cells to promote the repair of articular discs.…”
Section: Other Oral Diseasesmentioning
confidence: 99%
“…Se estima que la luxación mandibular corresponde al 3 % de las luxaciones articulares del cuerpo 6 . En un servicio de urgencia con aproximadamente 100,000 visitas anuales, se presentaron 37 casos de luxación mandibular durante un periodo de 7 años 7 .…”
Section: Introductionunclassified